Disputes in bioethics : abortion, euthanasia, and other controversies - Kaczor, Christopher, 1969- (Notre Dame studies in medical ethics., 2020)
"Disputes in Bioethics tackles some of the most debated questions in contemporary scholarship about the beginning and end of life. This collection of essays takes up questions about the dawn of human life, including: Should we make children with three (or more) parents? Is it better never to have been born? and Why should the baby live? This volume also asks about the dusk of human life: Is 'death with dignity' a dangerous euphemism? Should euthanasia be permitted for children? Does assisted suicide harm those who do not choose to die? Still other questions are asked concerning recent views that health care professionals should not have a right to conscientiously object to legal and accepted medical practices. Finally, the book addresses questions about separating conjoined twins as well as the issue of whether the species of an individual makes a difference for the individual's moral status. Christopher Kaczor critiques some of the most recent and influential positions in bioethics, while eschewing both consequentialism and principalism. Rooted in the Catholic principle that faith and reason are harmonious, this book shows how Catholic bioethical teaching is rationally defensible in terms that people of good will, secular or religious, can accept. Proceeding from a natural law perspective, Kaczor defends the inherent dignity of all human beings and argues that they merit the protection of their basic human goods because of that inherent dignity. Philosophers interested in applied ethics, as well as students and professors of law, will profit from reading Disputes in Bioethics. The book aims to be both philosophically sophisticated and accessible for students and experienced researchers alike."--